Business Registration Reform Case Study : Norway - International Finance Corporation (World Bank, Washington, DC, 2018)
Sustainable economic growth and reduction of poverty require a suitable framework of good governance. A register solution that works efficiently and offers reliable business information is an essential part of such a framework. To ensure efficiency and simplification in business start-ups, a well-functioning register solution has several beneficial effects. It encourages entrepreneurship, improves access to loans, generates more jobs, makes it easier to comply with rules, and reduces administrative burdens, thus increasing productivity. In a broader perspective, this helps attract investors, boost the economy in general, and reduce poverty. Implementation of good governance has revealed a general need to enhance transparency and integrity standards in public administrations and private entities. Availability of official, high-quality business information is crucial in this context. By granting the legal identity of a business, most register solutions go a step further. In doing so, they increase the predictability of economic interaction and provide contractual partners with core protection against abuse. This also reduces the costs of resolving disputes and leads to greater judicial fairness because of faster contract enforcement. Moreover, improved transparency contributes to more effective tracing of financial crime and therefore constitutes a means to prevent and discourage financial crime in general. In the Norwegian register solution, the aim of enhancing transparency is strongly interlinked with the objective of using public business information efficiently and reducing reporting obligations for businesses. Information sharing is an important building block in this strategy. This case study describes how reforms aimed at simplifying and streamlining business registration were implemented in Norway. It is based on desk research and interviews.